2019
DOI: 10.1080/10871209.2019.1563929
|View full text |Cite
|
Sign up to set email alerts
|

Community participation in ecotourism and its effect on local perceptions of snow leopard (Panthera uncia) conservation

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…By adopting a community-based conflict mitigation approach we have been successful in reducing human-leopard conflicts within a multi-use landscape of the Himalayan region. Similar success stories such as the “Lion Guardians” project in east Africa ( Hazzah et al, 2014 ), snow leopard community based conservation programs in India ( Vannelli et al, 2019 ), Tiger Team initiative in Bangladesh Sundarbans ( Inskip et al, 2016 ) and Persian leopard conservation project in Iran ( Khorozyan et al, 2017 ) have demonstrated considerable success in improving human-predator relations and created pathways of coexistence within developing regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…By adopting a community-based conflict mitigation approach we have been successful in reducing human-leopard conflicts within a multi-use landscape of the Himalayan region. Similar success stories such as the “Lion Guardians” project in east Africa ( Hazzah et al, 2014 ), snow leopard community based conservation programs in India ( Vannelli et al, 2019 ), Tiger Team initiative in Bangladesh Sundarbans ( Inskip et al, 2016 ) and Persian leopard conservation project in Iran ( Khorozyan et al, 2017 ) have demonstrated considerable success in improving human-predator relations and created pathways of coexistence within developing regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of jaguars (Panthera onca), Caruso et al (2020) found a similar pattern; people's perceptions and attitudes were strongly influenced by occupation and economic benefits through ecotourism. In Ladakh, India snow leopard based ecotourism has become popular and provides income generation opportunities to the local communities (Jackson, 2015;Maheshwari & Sathyakumar, 2019;Vannelli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Ecotourism is a lubricant to strengthen the linkage between conservation and communities' livelihood based on the notion that the needs of local people and the conservation goals can be reconciled (Boley and Green, 2016;Mathis and Rose, 2016;Ma et al, 2019). Despite the conflicted relationship between livelihoods and conservation goals, as a neo-liberal approach to sustainable development, it is argued that ecotourism is touted as a promising route for generating economic incentives, especially for those minority groups or local people and supporting biodiversity conservation simultaneously (Ramírez and Santana, 2018;Vannelli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%